2016
DOI: 10.1080/03075079.2016.1190961
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation, distinction and equality – or diversity? The language of the marketised university: an England, New Zealand comparison

Abstract: This paper examines how universities reconcile the need to project themselves as successful global competitors with the need to respond to national policy expectations, particularly around equality. It does so through a comparative analysis of the language used in the publicly available documents of universities in England and New Zealand. While a discourse of 'distinctiveness' is employed across the board by universities to denote superiority, there are differences in the extent to which differently ranked un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 39 publications
0
24
0
5
Order By: Relevance
“…Confirming these results, Seeber et al (2019) argue further that this trade-off depends not only on the institutional proximity between UK higher education institutions, expressed by the affiliation to a specific mission group (Russell group, 1994, Million+, University Alliance, GuildHE), but also on the geographic proximity between them. Bowl (2018), Jin and Horta (2018) and Huisman and Mampaey (2018) consider age and status of universities and illustrate how older and higher-status institutions prefer not to deviate from historically based institutional expectations, whereas younger and lower-status universities are more prone to unconventional positioning paths.…”
Section: Attempts At Balancing Conflicting Hypothesesmentioning
confidence: 99%
“…Confirming these results, Seeber et al (2019) argue further that this trade-off depends not only on the institutional proximity between UK higher education institutions, expressed by the affiliation to a specific mission group (Russell group, 1994, Million+, University Alliance, GuildHE), but also on the geographic proximity between them. Bowl (2018), Jin and Horta (2018) and Huisman and Mampaey (2018) consider age and status of universities and illustrate how older and higher-status institutions prefer not to deviate from historically based institutional expectations, whereas younger and lower-status universities are more prone to unconventional positioning paths.…”
Section: Attempts At Balancing Conflicting Hypothesesmentioning
confidence: 99%
“…Almost three quarters of university provision is at Bachelor's degree level (NZPC, 2017). Bowl (2018) proposes that universities employ a discourse of 'distinctiveness' to denote their academic superiority over other tertiary education institutions (for instance polytechnics, wānanga and competing universities) in order to promote themselves as successful global competitors to reap rewards from a competitive educational market vying for student enrolments.…”
Section: Universitiesmentioning
confidence: 99%
“…There is wide acknowledgement of the marketisation environment which has caused universities to become more image-conscious with branding, self-promotion, impression management and competition for research funds (Bowl, 2018;Rowe-Williams, 2018). One example of marketisation is the obsession with the global ranking of universities across the world.…”
Section: Universitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…More recent studies have also indicated that the concept of diversity, as deployed within many educational institutions, can have the effect of sustaining inequalities (see Talib and Fitzgerald (2015), for example, in relation to the schools sector). On the basis of her analysis of publically-available statements from higher education institutions in New Zealand and the UK, Bowl (2018) contends that commitments to equality have been side-lined in favour of those that focus on diversity. She maintains that this linguistic change helps HEIs mediate the tension between 'the need … to project themselves as strong competitors in a global market and leading contributors to the knowledge economy, while at the same time responding to national policy requirements to widen the social base of higher education' (p.672).…”
Section: Introductionmentioning
confidence: 99%